Optimalisasi Kinerja Perawat melalui Peningkatan Kemampuan Pengambilan Keputusan Klinis - Reski Indahyani; Samsualam; Akbar Asfar (Window of Nursing Journal, 2026)
A nurse is a person who interacts with patients 24 hours a day, guided by the nursing process. The ability to make decisions in providing nursing care is one of the requirements for nurses to carry out professional nursing practice. Decision making is a systematic approach to solving a problem. The aim of this research is to determine the influence of ability and skill in making decisions on improving the performance of hospital clinical nurses. The research design used is correlation. The population is human resources at Ibnu Sina Hospital Makassar. A sample of 30 respondents was taken using Total Sampling. The independent variable is the ability and skill in making decisions. The dependent variable is nurse performance. Data was collected using questionnaires and interviews, then analyzed using multiple logistic regression with α=0.05. The statistical test results of the influence of ability and skill in making decisions are ρ= 0.03 (ρ<α) which means that there is an influence of ability and skill in making decisions on improving the performance of clinical nurses. The conclusion of this research is that there is an influence of ability and skill in making decisions on improving the performance of clinical nurses at Ibnu Sina Hospital Makassar.